The organic waste management supply chain performance evaluation strategy uses an Interpretive Structural Modeling approach - Arsiwi, Pramudi; Setyaningrum, Ratih; Talitha, Tita; Ramdhani, Safarudin (OPSI, 2024)
National Waste Management Information System shows that the amount of waste handled in Semarang City over the last three years has decreased with an average decline index of 1.06% per year. This is reinforced by the results of interviews with the Semarang City Environmental Service, that the handling of organic waste is still very limited because so far the handling has been more focused on an-organic waste. Therefore, it is necessary to evaluate supply chain performance to determine the constraints in organic waste management from upstream to downstream. Based on the research results using the Interpretive Structural Modeling (ISM) method through a focus group discussion process involving eight experts in the field of waste management, it is known that the supply chain performance for handling organic waste in Semarang City has 11 elements of constraints, which are divided into seven priority levels. The element with the highest priority is related to the availability of organic waste supplies, while the element with the lowest priority is technological innovation and the application of appropriate technology. Improving the performance of organic waste management supply chains should focus on elements according to priority.